Women's acceptability of a self-collect HPV same-day screen-and-treat program in a high burden setting in the Pacific - Hawa Camara; Somu Nosi; Gloria Munnull; Steven G. Badman; John Bolgna; Joseph Kuk; Glen Mola; Rebecca Guy; Andrew J. Vallely; Angela Kelly-Hanku (BMC, 2022)
Abstract Background A field trial to evaluate a self-collect point-of-care HPV screen-and-treat (HPV S&T) program was implemented in two Well Women Clinics in Papua New Guinea (Papua New Guinea). Assessing the acceptability of a health intervention is a core element of evaluation. In this study, we examined women's acceptability of both self-collection and HPV S&T intervention in Papua New Guinea.  Methods Sixty-two semi-structured interviews were conducted with women who had undergone cervical screening in the same-day self-collected HPV screen-and-treat program in Madang and Western Highlands Provinces, Papua New Guinea. Data were thematically analysed using the Theoretical Framework of Acceptability (TFA) and managed using NVivo 12.5. Results Most women agreed that self-collection was transformative: it helped circumvent the culturally embarrassing pelvic examination and increased their self-efficacy, especially due to the provision of health education, instructions, and pictorial aids. The availability of same-day results, and treatment if indicated, was particularly valued by the women because it reduced the financial and temporal burden to return to the clinic for results. It also meant they did not need to wait anxiously for long periods of time for their results. Women also appreciated the support from, and expertise of, health care workers throughout the process and spoke of trust in the HPV-DNA testing technology. Most women were willing to pay for the service to ensure its sustainability and timely scale-up throughout Papua New Guinea to support access for women in harder to reach areas. Conclusion This study reported very high levels of acceptability from a field trial of self-collection and HPV same-day screen-and-treat. The program was deemed culturally congruent and time efficient. This innovative cervical screening modality could be the 'solution' needed to see wider and more immediate impact and improved outcomes for women in Papua New Guinea and other high-burden, low-resource settings.